SYMBOLISM OF WATER IN HINDU LITERATURE: FROM SARASWATI TO TIRTA AMERTA - Ida Ayu Komang Arniati; I Ketut Suda (International Conference on Multidisciplinary Research Perspective, 2025)
Water in the Hindu tradition not only serves as a physical element that sustains life, but also as a symbol of purity, knowledge, and spiritual transformation. This research aims to examine the symbolism of water in Hindu sacred texts — the Rigveda, the Bhagavad Gītā, and the Purāṇa — as well as to trace its manifestation in the ritual and cultural practices of the Balinese Hindu community. The study was conducted with a qualitative-descriptive approach through textual analysis and symbolic interpretation, using the theory of religious symbols from Mircea Eliade and Émile Durkheim. The results show that water in the Rigveda is seen as the source of life and cosmic harmony; in the Bhagavad Gītā, water is the embodiment of God’s presence in the material world; while in the Purāṇa, the myth of Tirta Amerta affirms water as a symbol of immortality and wisdom. This finding finds its actualization in the tirtha tradition in Bali which serves as a medium of purification and ecological ethics. The symbolism of water in this context shows the integration between theology, culture, and ecological consciousness, and provides the basis for the development of Hindu environmental theology (eco-theology) that is relevant to the challenges of modern times.